Analysis of Heavy Rainfall Using Radar Image Data, Satellite Images, and Rainfall Stations in the City of Padang - Ferdi Agusrianto; Nofi Yendri Sudiar; Harman Amir; Zulhendra (Journal of Climate Change Society, 2026)
Padang City, as the capital of West Sumatra Province, often experiences heavy rains that can cause flooding and landslides. This phenomenon of heavy rainfall is a matter of serious concern due to its impact on the lives of the community, infrastructure, and the regional economy. On March 7, 2024, heavy rainfall occurred in Padang City, triggering flooding and causing loss of life and property. The analysis was conducted using weather radar imagery, satellite imagery, and rainfall observation data from several rain gauges in Padang City. To obtain representative rainfall data with broad spatial coverage, the use of remote sensing data such as weather radar images and satellite images is vital, especially for areas with a limited number of rain stations or difficult-to-reach topography. Therefore, this study aims to analyze the comparison of rainfall data based on radar imagery, satellite imagery, and rain gauge data to understand the advantages and limitations of each instrument. The combination of these three data sources is very important to improve the accuracy of rainfall monitoring. The research method used in this study is quantitative research using data from the BMKG. The results of the analysis obtained from the error and correlation, both from radar data and satellite imagery, generally show a tendency to underestimate the rainfall observed at rain gauges in Padang City, as indicated by the Mean Error (ME) value, which is predominantly negative at almost all rain gauges.